The effects of visual imagery on face identification: an ERP study - Wu, Jianhui; Duan, Hongxia; Tian, Xing; Wang, Peipei; Zhang, Kan (Frontiers in Human Neuroscience, 2012)
The present study tested the hypothesis that the effects of mental imagery on subsequent perception occur at a later matching stage in perceptual identification, but not in the early perceptual stage as in perceptual detection. The behavioral results suggested that the effect of visual imagery on visual identification is content-specific, i.e., imagining a congruent face facilitates face identification, whereas a mismatch between imagery and perception leads to an interference effect. More importantly, the ERP results revealed that a more negative N2 response to the subsequent visual face stimuli was elicited over fronto-central sites in the mismatch and no-imagery conditions as compared to that in the match condition, with the early P1 and N170 components independent of manipulations. The latency and distribution of the neural effects demonstrate that the matching step, but not the earlier perceptual process, is affected by the preceding visual imagery in the context of face identification. We discuss these results in a broader context that the imagery-perception interaction may depend on task demand.